Design and Synthesis of Surface Acoustic Wave Ladder-Type Filter With Prescribed Group Delay - LIM , ANDREW ZHI LUN (2018)
There are three kinds of Surface Acoustic Wave (SAW) filter design which are the Interdigitated Interdigital Transducer (IIDT) type design, Double Mode SAW (DMS) type design and ladder-type design. However, this study will focus on the SAW ladder-type filter with prescribed group delay as synthesis approach is applied to obtain a ladder filter with specific group delay network. A SAW ladder-type filter consists of one-port SAW resonators connected in series and shunt to obtain a bandpass filter (BPF) response. Therefore, the modeling of one-port SAW resonator using its equivalent circuit is conducted to investigate the relationship between the resonator structure and the lumped element parameters. The band-pass LC channel is outlined in light of the conventional Bessel channel plan. At that point, LC resonators in the channel are supplanted by SAW resonators with limited capacitance proportion γ. Limited γ creates passband swells in the gathering delay. ADS is chosen to coordinate the reaction of estimated SAW resonator with its identical circuit. The ability to build in transmission zeros at finite frequencies can improve the close-to-band rejection slope in term of high selectivity, and/or enhance the linearity of in-band group delay. In this paper, the synthesis is developed and presented together with the required canonical low-pass circuit forms and corresponding transmission zeros that the transfer functions may realize. The procedure for different low-pass filter degrees is included with the required circuit transformations which was a significant piece of work. Design examples are included to illustrate the synthesis technique.